A KHALED ABOU EL FADL'S HERMENEUTICS IN UNDERSTANDING ARABIC TEXTS - Muhammad Abdur Rozaq (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
This article discusses Khaled Abou El Fadl's hermeneutical approach in understanding Arabic texts, especially religious texts such as the Qur’an and hadist. Abou El Fadl emphasizes the importance of understanding texts through three main elements: text, historical context, and the role of the reader. He criticized the literal approach which often ignores the complexity of the Arabic language, moral values ??and the objectives of Islamic law. This research uses library research, which focuses on analyzing textual data from primary and secondary sources with a descriptive qualitative approach which aims to describe and analyze the concept of hermeneutics from Khaled Abou El Fadl's perspective, with a focus on theoretical and applicable contexts. In his approach, Abou El Fadl highlights the importance of negotiating meaning between the reader and the text, the use of in-depth linguistic analysis, and intertextual understanding to reveal the message of justice contained in the text. This article also presents examples of relevant verses from the Qur'an and hadith to show how this hermeneutical approach is applied. By emphasizing the principles of justice and intellectual honesty, Abou El Fadl's hermeneutics makes an important contribution in interpreting Islamic texts contextually and inclusively in the contemporary era.